Investigation of Effective Microorganism (Em-Mudball) in raw water treatment - Muhammad Ariff Azwan, Azmi; Mohd Najib, Razali; Najmuddin, Mohd Ramli; Obi, Nasreldeen Ishag; Anuar, Amira Ermafiqka (IET, 2022)
EM-mudball is a green technology product used to treat raw water by using effective microorganisms. The use of EM-mudball can alter the compositions of prop- erties in raw water and improve water quality. Three different EM-mudball ratios were created out of soil/clay, Bokashi compost, and EM 1 compositions in 1:1:1, 1:2:1, and 1:2:2 ratios, respectively.The mudball undergoes the characterization test to observe the presence of fungi and bacteria. Additional 2 different ratios of EM-Mudball were bought from the market as to compare its performance. This mudball was tested into two different raw water samples, taken from a river and a well. Two liters of each raw water types were put in a plastic container and tested with the EM-mudball. Then, the mudball was set in the raw waters for 14 days for the effective microorganisms to react. The best result from the analysis of well water is from Industrial B and simula- tion 1 EM-mudball based on 6 parameters and the biochemical oxygen demand (BOD) value reduction is 3.92 mg/L and 4.68 mg/L respectively, chemical oxygen demand (COD) at 38 mg/L and 44 mg/L respectively, turbidity were 7 and 9 NTU respectively and the pH value was maintained at the optimum value of 7.32 and 7.41 respectively. However, the EM-Mudball is unable to reduce the ammonia Cal nitrogen (AN) and total suspended solids (TSS) and maintain its initial state. In conclusion, as an overall result, this water treatment method is able to improve the quality of water by treating thoseparameters.